Water and Nutrient Recovery for Cucumber Hydroponic Cultivation in Simultaneous Biological Treatment of Urine and Grey Water - Anna Wdowikowska; Małgorzata Reda; Katarzyna Kabała; Piotr Chohura; Anna Jurga; Kamil Janiak; Małgorzata Janicka (Plants, 2023)
Water and nutrient deficiencies in soil are becoming a serious threat to crop production. Therefore, usable water and nutrient recovery from wastewater, such as urine and grey water, should be considered. In this work, we showed the possibility of using grey water and urine after processing in an aerobic reactor with activated sludge in which the nitrification process takes place. The resulting liquid (nitrified urine and grey water, NUG) contains three potential factors that can adversely affect plant growth in a hydroponic system: anionic surfactants, nutrient deficits, and salinity. After dilution and supplementation with small amounts of macro- and micro-elements, NUG was suitable for cucumber cultivation. Plant growth on this modified medium (enriched nitrified urine and grey water, NUGE) was similar to that of plants cultivated on Hoagland solution (HS) and reference commercial fertilizer (RCF). The modified medium (NUGE) contained a significant amount of sodium (Na) ions. Therefore, typical effects of salt stress were observed in cucumber plants, including reduced chlorophyll levels, slightly weaker photosynthesis parameters, increased H2O2 levels, lipid peroxidation, ascorbate peroxidase (APX) activity, and proline content in the leaves. In addition, reduced protein levels were observed in plants treated with recycled medium. At the same time, lower nitrate content in tissues was found, which may have resulted from their intensive use by nitrate reductase (NR), the activity of which significantly increased. Although cucumber is a glycophyte, it grew very well in this recycled medium. Interestingly, salt stress and possibly anionic surfactants promoted flower formation, which in turn could positively affect plant yield.